Challenges to healthy eating practices: A qualitative study of non-Hispanic black men living with diabetes - Lee, Loretta T. (Diabetes Educ, 2016)
PURPOSE: The purpose of this study was to explore current dietary practices and perceived barriers to healthy eating in non-Hispanic black men with type 2 diabetes. METHODS: Four 90-minute focus groups held in September and October, 2011 were led by a trained moderator with a written guide to facilitate discussion on dietary practices and barriers to healthy eating. Participants were recruited from the diabetes database at a public safety-net health system in Jefferson County, Alabama. Two-independent reviewers (LTL and ALW) performed content analysis to identify major themes using a combined deductive and inductive approach. RESULTS: There were 34 male participants aged 18 years and older. Mean years living with diabetes was 9.6 ± 5.9. Sixty-two percent of participants perceived themselves to be in fair or poor health. Participants’ self-reported eating practices did not always relate to hunger. Internal cues to eat included habit and response to emotions; and external cues to eat included media messaging, medication regimens, and work schedules. Men identified multiple barriers to healthy eating including hard-to-break habits, limited resources and availability of food at home and in neighborhood grocery stores, and perceived poor health-care professional communication. CONCLUSION: Non-Hispanic black men acknowledged the importance of healthy eating as part of diabetes self-management, but reported various internal and external challenges that present barriers to healthy eating. Tailored strategies to overcome barriers to healthy eating among non-Hispanic black men should be developed and tested for their impact on diabetes self-management.